Appropriately Uncomfortable: A Conversation Among Three Colleagues About Structural Oppression Focusing on Racism and the Need for Action - Aguilar, Jemel; Smith, Carmela Fusciello; Tomczak, Stephen Monroe (Reflections: Narratives of Professional Helping, 2021)
In this reflection, three social work colleagues discuss three different perspectives on one statement about racism. We detail our emotionally challenging conversations about racism, microaggressions, and the meaning of social justice in social work to build a different bond and sense of understanding. We delve into how we understand each other, our differing viewpoints on the murders of Black people in American society such as George Floyd, and our perspectives on social workers’ relationships to social justice, racism, and social change in the context of the 2020 turmoil.
Keywords: dept.swk; higher education; oppression; peer-reviewed; racism; social work faculty

Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach - Aguilar, Jemel; Carpenter, Elisabeth Counselman (Cognella Academic Publishing, 2021)
Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach challenges the socialization of preservice social workers by examining the complex features of individuals, families, groups, and societies and how they present themselves within the context of the multiple and simultaneous influences on behavior, cognitions, and emotions.This text is divided into three distinct units. Unit I development at the individual level and the influences that shape human behavior, including adverse childhood experiences, identity development through social media, resilience, and chronic illness. Unit II focuses on interpersonal dynamics with articles that explore grief theories, the transgender experience, intergenerational trauma, privilege, and more. Unit III examines structural social systems such as institutional racism, religious-based prejudice, and structural violence.Written to help social work students and professionals begin the process of decolonizing their education and practice, Decolonizing Human Behavior in the Social Environment is an essential and timely reader for courses and programs in social work. It is also an exemplary resource for practitioners at all levels.
Keywords: dept.swk

Transitional Challenges in Technology Adoption among Academic Communities in Indian Higher Education Institutions - N, Elangovan; Yeon, Guydeuk; PERUMBILLY, SEBASTIAN; AWUNGSHI, SARAH HORMEILA (Journal of International Technology and Information Management, 2021)
Keywords: dept.mft; peer-reviewed

Bilingual Court Professionals’ Perceptions of Their Language Skills: Asset or Liability? - Logan, Isabel; Negroni, Lirio K. (Advances in Social Work, 2021)
Bilingual professionals are considered an asset in the workplace. However, bilingual professionals at times perceive their language skills as a liability. This paper examined bilingual professionals’ perceptions of their language skills and the factors that influence their views. Focus groups were used to capture the perspectives of 15 bilingual professionals who speak English and Spanish and work in a court system in the eastern region of the United States. Findings reveal challenges rooted in discrimination that convert bilingual professionals’ perceptions of their language skills from an asset to a liability. Participants highlight unfair practices affecting Limited English Proficiency (LEP) clients. These practices force bilingual professionals to become protectors and gatekeepers to prevent adverse outcomes and provide access to services in the court and across social service systems. Ultimately, bilingual professionals’ perceptions of their language skills depended on how others used their language skills in the workplace. To support bilingual professionals and provide quality services to LEP clients, social work administrators must evaluate structural supports and provide training specific to the cultural aspect of language for all employees.
Keywords: Bilingual Professionals; Court system; Discrimination; Language; Social Work; dept.swk; peer-reviewed

Book Review: Free Cyntoia: My search for redemption in the American prison system: - Smoyer, Amy B. (Affilia, 2021)
Keywords: book.review; dept.swk; peer-reviewed

Best practices for assessing digital literacy and strengthening online teaching pedagogy of digitally immigrant stakeholders in higher education - Counselman-Carpenter, Elisabeth; Aguilar, Jemel P. (Springer International Publishing, 2021)
Keywords: dept.swk

‘The mirage of action’: Exploring the social work professions’ perpetuation of white supremacy through ‘Well-Intentioned’ actions - Aguilar, Jemel P.; Counselman-Carpenter, Elisabeth (Advances in Social Work, 2021)
This autoethnographic study highlights complex strategies for maintaining white supremacy used by “well-intentioned” heterocentric white female social workers that are enacted under the guise of practicing anti-racism in social work practice settings, classroom environments, policy initiatives, and advocacy work. Using autoethnography was both unplanned and deliberate. Unplanned, we needed a research method that allows us to explore the untouchable subject of heterocentric white female social workers and deliberate in that we could use our experiences to break ground and establish white supremacy among heterocentric white female social workers that espouse anti-racist values as an area of study. We draw on education, anthropology, sociology, and other disciplines to name some of the ongoing challenges to dismantling racism, colonialist, and reformer narratives in social work, and identify strategies used by all white folx, but particularly heterocentric white female social workers to neutralize the suggestion or accusation of their acts as racism. We name three challenges to dismantling racism among heterocentric white female social workers: hiding behind the data, anti-racist book clubs, and crying and comfort. We conclude with further questions for those who hold power in the field and a reflection upon our own continued intersecting struggles with these concepts. © 2021 Authors,.
Keywords: dept.swk; peer-reviewed

Deepening the learning: Intersectional experiential activities to address white supremacy - Keenan, Elizabeth King; Kozu, Shuei; Mayhew, Hunter; Saiter-Meyers, Evelyn; Meggett, Caliyah; Reynolds, Paige (Advances in Social Work, 2021)
Graduate students of multiple racial identities in predominantly White institutions enter social work programs with a wide range of knowledge about and experiences of White Supremacy, particularly the ways in which structural forms of racism continue to inflict harm, block opportunities, and perpetuate wealth inequities. In addition, White students are often challenged to grasp the ways they have been socialized to participate in perpetuating White Supremacy. This wide range of knowledge and experiences makes it likely that students will experience a range of emotions and defensive resistance necessitating skillful pedagogical design and facilitation of class interactions. Intentional use of theoretical frameworks with experiential activities can deepen self-awareness and understanding of the systemic nature of White Supremacy (Okun, 2010). In this manuscript, four students and two instructors discuss their learning experiences within a course addressing White Supremacy for students of multiple racial identities in a predominantly White institution. Post-course dialogue amongst these multiracial authors identified six core areas of learning when examining intrapersonal, interpersonal, and structural racism, cultural wealth of BIPOC peoples, and anti-racism actions. Two primary implications for education are: Weave conceptual frameworks with interpersonal experiential activities throughout the course design, and attend to interactional power dynamics during class meetings. © 2021 Authors, Vol. 21 No. 2/3 (Summer 2021), 821-840,.
Keywords: dept.swk; peer-reviewed

Healthcare-induced trauma in correctional facilities: a qualitative exploration. - Elumn, Johanna; Keating, Layne; Smoyer, Amy B.; Wang, Emily A. (Health & justice, 2021)
Background: While incarcerated people are known to experience trauma at higher rates than the general population, little is known about how the correctional health system contributes to trauma rates. Methods: We conducted 20 semi-structured qualitative interviews with men who were recently released from a correctional system to understand their experiences with healthcare systems and medical staff during incarceration. Using reflexive thematic analysis within a critical realist framework, we coded and analyzed the data iteratively to refine and unify emerging themes. Results: The unanticipated concept of healthcare-induced trauma emerged and was revealed in three overall themes: (1) healthcare leading to fear of serious illness or death, (2) healthcare leading to fear of people, including healthcare providers, correctional staff, and other incarcerated people, and (3) the correctional institutional, social, and physical environment leads to fear of place. Conclusions: Healthcare in correctional settings has the potential to induce trauma, even when the medical conditions addressed are not life-threatening. Future research should examine the factors contributing to the development of healthcare-induced trauma in correctional settings and develop interventions to prevent and address this phenomenon. © 2021, The Author(s).
Keywords: dept.swk; peer-reviewed

Growing up in the age of COVID-19 through the lens of psychodynamic theory - Grady, Melissa D.; O’Toole, Randall; Schneider, Dana A. (Psychoanalytic Social Work, 2021)
The long-term effects of the global COVID-19 pandemic on individuals, families, and society are not yet known. For social workers, it is critical to consider how the pandemic is impacting families, and in particular, children and their development. This manuscript applies psychodynamic theory and research on neurobiology to explore some of the potential effects of COVID-19 on children and their developmental trajectories. The discussion of these psychodynamic concepts is also placed within the context of the heightened tensions around equity and social justice issues within the U.S. society. In addition, this article provides guidelines, strategies, and resources for social workers that can be used when working with families and caregivers to mitigate any potential negative effects that the pandemic is having on children and their families. A case presentation is included to further illustrate these issues. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.swk; peer-reviewed

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

The past and future of social group work in Germany: contributions of Louis Lowy - Gardella, Lorrie Greenhouse (Social Work with Groups, 2021)
Louis Lowy (1920 to 1991), the international social work educator, remembered surviving the Holocaust as a formative professional experience. After joining the faculty of Boston University School of Social Work, Lowy returned to Germany every summer for 20 years to help restore social work education. This SPARC project, “The Past and Future of Social Group Work in Germany: Contributions of Louis Lowy,” was proposed in collaboration with Klaus-Martin Ellerbrock and the German Chapter of IASWG at the height of the 2015 global refugee crisis, when Germany admitted more than one million refugees. The purposes of the project were to encourage ongoing international scholarship on the implications of Lowy’s teachings for social work with groups; to facilitate research and writing from an international perspective on group work with migrants and other disenfranchised populations; and to foster international collaborations among group workers in the spirit of Louis Lowy. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.swk; peer-reviewed

Masculine embodiment among sexual minorities in a women’s prison - Smoyer, Amy B.; Divita, David; Perrault, Allison (Australian Social Work, 2021)
Sexual minority women are disproportionately incarcerated and more likely to experience structural and interpersonal violence while incarcerated than heterosexual cisgender women. To build knowledge about this population and inform social work practice, theories of embodiment were used to conduct thematic analysis of five interviews with lesbian, gay, bisexual, transgender, and queer masculine-identified people who had been incarcerated in a women’s prison. This analysis explicates how participants used bodily practices to construct gender and communicate identity to themselves and others. Uniforms, prison regulations, and physical manifestations of female embodiment complicated these efforts. Participants described the ways in which they monitored and evaluated their own bodies while also managing the constant surveillance of their bodies by others. Taken together, these findings explicate the ways in which participants’ bodies were produced both through their actions and the external gaze of others. Implications for social work include exploration of language and masculinity in practice settings and suggestions for correctional policies. Findings encourage inclusion of non-binary frameworks and increased attention to the embodied self in order to expand understandings of human behaviour in the social environment. IMPLICATIONS Interpret with caution any information about gender identity surmised from intake forms and observation of clients’ bodily practices. Ask clients to describe their gender identity. Prioritise correctional policies that promote the health and safety of incarcerated people and staff over policies that enforce social norms related to gender and have no implications on security. Encourage re-entry service providers to collaborate with LGBTIQA+ organisations that provide social support to clients who identify as sexual minorities. © 2021 Australian Association of Social Workers.
Keywords: LGBTQIA+ people; adult; article; attention; correctional facility; dept.swk; female; gaze; gender identity; human; interview; language; male; masculinity; organization; peer-reviewed; security; social environment; social norm; social support; social work practice; thematic analysis

‘Suppression on top of oppression’: A symbolic interactionist perspective on the affective experience of incarceration - Umamaheswar, Janani (The British Journal of Criminology, 2021)
Penological research has extensively documented how incarcerated men's identities are shaped by the prison setting, highlighting how these men cope with and adapt to the 'pains of imprisonment' through careful emotion management. Significantly less research has focused explicitly on the role of emotion in incarcerated men's constructions of their selves. In this article, I draw on 24 in-depth interviews with incarcerated men to reveal how the prison setting generates negative emotions (such as sadness, shame, humiliation, and anger) that in turn perpetuate the isolation that these men face. Emotions thus constitute an overlooked source of these men's social marginalization. Additionally, I draw on theoretical literature derived from symbolic interactionism (and identity theory in particular) to explore how participants cope with, and make efforts to overcome, their negative emotions by engaging in active emotion and identity work centred on constructing morality narratives of pride, self-worth, and superiority. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of the Centre for Crime and Justice Studies (ISTD). All rights reserved.
Keywords: dept.swk; peer-reviewed

Helps my family survive hard times: An innovative summertime food relief program in new haven, connecticut - Zigmont, V.A.; Tomczak, S.M.; Bromage, B.; Vignola, A.; Gallup, P (Journal of Poverty, 2021)
To achieve healthy communities, addressing food insecurity (FI) is critical. This study describes a unique food distribution program combining a mobile Summer Food Service Program (SFSP) for children with a mobile pantry for adults. A survey (n = 153) of participants at six locations in New Haven Connecticut revealed that 36% reported FI and 76% were first-time pantry users. Three- quarters participated in SNAP, WIC, or both, and two-thirds had children who were fed by SFSP. Major federal programs do not eliminate FI, therefore local voluntary organizations are essential partners to address the food crisis caused by the COVID-19 pandemic.
Keywords: dept.pch; dept.swk; peer-reviewed

Re/Un/Discover: An embodied heuristic for uncertainties in social work practice - Keenan, Elizabeth King (Australian Social Work, 2021)
Social workers have always worked with and within uncertainties in practice, but the COVID-19 pandemic is amplifying the frequency and degree of uncertainty across ecological levels. Social workers need enhanced capacity to work with these uncertainties and the impact on individual and collective wellbeing. The RE/UN/DIScover heuristic guides social workers’ responses to the wide range of practice uncertainties experienced in the moment and over time. Drawing on understandings of embodied wellbeing from interpersonal neurobiology and the power relations manifest in intersectional positionality, RE/UN/DIScover offers embodied, iterative practices to access the wealth of capabilities within self and others. IMPLICATIONS Disruptions and uncertainties connected with pandemics, economic recessions, continued systemic injustices and other human-made problems can challenge social workers and impact the wellbeing of individuals and communities. Heuristics are guides that sort, order, and inform decisions and actions. The RE/UN/DIScover heuristic uses knowledge about embodied wellbeing and various forms of power to guide social workers. RE/UN/DIScover offers social workers practices to use with uncertainties both in the moment and over time. © 2020 Australian Association of Social Workers.
Keywords: dept.swk; peer-reviewed

An ecological framework for understanding HIV- and AIDS-related stigma among Asian American and Pacific Islander men who have sex with men living in the USA - Sen, Soma; Aguilar, Jemel P.; Petty, Mac (Culture, Health and Sexuality, 2021)
Despite the fact that HIV- and AIDS-related stigma is consistently identified as an impediment to HIV prevention, a multilevel conceptualisation of HIV- and AIDS-related stigma continues to be poorly understood. The role of multilevel HIV- and AIDS-related stigma in the HIV prevention and intervention behaviours of Asian American and Pacific Islander who have sex with men in the USA is particularly overlooked. Psychology has contributed significantly to the identification of individual or interpersonal level factors influencing HIV- and AIDS-related stigma, while sociology has contributed to a more societal perspective. This dichotomy has led to the absence of a multilevel conceptual framework for analysing the HIV- or AIDS-related stigma experienced by Asian American and Pacific Islander who have sex with men in the USA. In this paper, we argue for need to develop such a model which is culturally grounded and bridges the individual, interpersonal and societal conceptualisations of stigma prominent in the social science literature. To that end, we use Bronfenbrenner’s ecological systems theory to explore the manifestation of HIV stigma at the micro, meso and macro levels and how these might impact on HIV testing and HIV service utilisation among Asian American and Pacific Islander men who have sex with men. We conclude by identifying some practice and research implications.
Keywords: Acquired Immunodeficiency Syndrome; Asian American; Asian Americans; HIV Infections; Homosexuality; Human immunodeficiency virus infection; Humans; Male; Sexual and Gender Minorities; United States; acquired immune deficiency syndrome; dept.swk; human; male; male homosexuality; peer-reviewed; sexual and gender minority

The everything else - Smoyer, Amy B. (Sensory Penalities, 2021)
Sensory Penalties aims to reinvigorate a conversation about the role of sensory experience in empirical investigation. It explores the visceral, personal reflections buried within forgotten criminological field notes, to ask what privileging these sensorial experiences does for how we understand and research spaces of punishment and social control.
Keywords: dept.swk

“When my mother died, I think a part of me died:” maternal fusion and the relationship between incarcerated men and their mothers - Umamaheswar, J. (Journal of Family Issues, 2021)
Drawing on theoretical literature on the mothering discourse, I explore how incarcerated men give meaning to their relationships with their mothers. Using 24 in-depth interviews with incarcerated adult men, I argue that adherence to the mothering discourse results in sons holding their mothers’ maternal practices to impossibly high standards while simultaneously feeling obligated to reconcile with their mothers even when doing so is tremendously difficult. I also advance the concept of “maternal fusion”—the process through which the identities of mothers and their children are intertwined—to examine how incarcerated adult sons reproduce gendered mothering ideologies in their narratives of (a) negative early childhood and adolescent relationships with their mothers and (b) reconciliation as they reflect on their relationships with their mothers as adult sons.
Keywords: adolescent; adult; article; child; childhood; dept.soc; dept.swk; drawing; female; human; human experiment; ideology; incarceration; infant; interview; male; maternal fusion; mother; mothering; mothering discourse; narrative; peer-reviewed; theoretical study

Build the social justice bridge: participatory photography with the international group work community - Gardella, L.G.; Prinsloo, R. (Social Work with Groups, 2021)
“Build the Social Justice Bridge” was a participatory photography project that engaged international group workers in an assessment of group work as a social justice profession. Inspired by principles of photovoice research, the project invited social work students, educators, and practitioners from around the world to contribute photographs and brief narratives that represented the relationship between group work and social justice. The photographs were exhibited during the opening session of the 2018 Symposium of the International Association for Social Work with Groups (IASWG) in South Africa, where more than 200 participants from ten countries reflected on the meaning of the photos for the group work community. In viewing the photos, symposium participants identified a common vision of social justice as well as culturally-specific approaches to group work. Implications are drawn for the internationalization of professional knowledge. © 2019 Taylor & Francis Group, LLC.
Keywords: South Africa; adult; article; dept.swk; female; human; human experiment; major clinical study; male; narrative; peer-reviewed; photography; physician; professional knowledge; social justice; social work student; vision; worker